Strategi penanganan korban kekerasan seksual pada perempuan oleh Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana Kabupaten Karanganyar - Amanda, Yesita; Rekejiningsih, Triana; Yuliandari, Erna (Academy of Education Journal, 2024)
This study aims to analyze: 1) What is the strategy for handling victims of sexual violence against women by the Office of Women's Empowerment, Child Protection, Population Control and Family Planning, Karanganyar Regency. 2) What are the problems encountered in handling victims of sexual violence against women and the solutions. In this study using qualitative research methods. In this study the results were found: 1) strategies for handling victims of sexual violence against women by the Office of Women's Empowerment, Child Protection, Population Control and Family Planning in Karanganyar Regency, namely (1) receiving reports, (2) outreach to victims, (3) case processing, ( 4) mediation, (5) medical, psychological, legal assistance, (6) psychological and trauma recovery. 2) The problems encountered in handling victims of sexual violence against women and their solutions are (1) lack of companion staff, namely by engaging other institutions that have the same goals, (2) victims who are not open, overcome with refreshing minds, (3) families who lack cooperative given an understanding, (4) the lack of understanding of the community about the agency that handles cases of sexual violence, overcome by conducting socialization.